Aqsam Al-quran ( sumpah-sumpah dalam al-quran) - Putri Adinda; Hambali Hanafiah; Annisa Septriana Putri; Riska Sawitri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
ABSTRACT This study explores the concept of Aqsam al-Qur’an, which refers to the oaths mentioned in the Qur’an, emphasizing their linguistic, theological, and pedagogical functions in conveying divine messages and reinforcing truth. The research aims to examine the meaning, usage, elements, and types of qasam in Al-Qur’an, and to understand how these oaths serve as tools for strengthening faith, moral guidance, and comprehension of Islamic teachings. Employing a qualitative research method through literature review, the study analyzes primary sources from the Qur’an and secondary sources including tafsir and scholarly works related to ulumul Qur’an. The results reveal that qasam is structured strategically with specific linguistic forms such as fi’il, muqsam bih, and muqsam ‘alaih, with varying types including zhahir and mudhmar, to ensure clarity, conviction, and effective communication of divine guidance. These findings demonstrate that oaths are not merely rhetorical devices, but play a crucial role in shaping believers’ understanding and behavior. Consequently, this research contributes to the enrichment of Qur’anic studies and provides a framework for integrating the pedagogical use of qasam in Islamic education. Keywords Al-Qur’an, Aqsam, Islamic education, Oaths, Qasam.